Surgical Morbidity in Relation to the Surgical Approach for Olfactory Groove Meningiomas—A Pooled Analysis of 1016 Patients and Proposal of a New Reporting System - Ekkehard M. Kasper; Farhan A. Mirza; Serdar Kaya; Robert Walker; Daniele Starnoni; Roy T. Daniel; Ramesh Nair; Fred C. Lam (Brain Sciences, 2023)
Background: There is currently no consensus in the field regarding whether a frontal or lateral approach is superior for microsurgical resection of olfactory groove meningiomas (OGM). Due to the lack of uniformity in classifying lesions and inherent differences in reporting outcomes after varying operative approaches, the best practice for approaching these lesions is yet to be determined. Objective: This study aimed to assess various surgical approaches undertaken for OGMs, investigate procedural aspects influencing the extent of resection, and analyze the respective complication rate associated with each approach. We performed a comprehensive literature review of presenting signs and symptoms in OGM patients, their surgical management, and the reported surgical outcomes. To address the lack of uniform data reporting across studies and to take more recent translational studies into account, we developed a new classification system for OGMs that can remedy the existing deficiencies in comparability of reporting. Methods: We conducted a PRISMA-guided literature search for surgical reports on OGMs published in the MRI era using broad search terms such as ‘olfactory groove meningioma’ and ‘surgery’, which yielded 20,672 results. After title screening and removal of duplicates, we assessed 871 studies on the specific surgical management of olfactory groove meningiomas. Following the application of exclusion criteria and abstract screening, a set of 27 studies was chosen for the final analysis of a pooled cohort of these reported patient outcomes. Results: The final twenty-seven studies included in our in-depth analysis identified a total of 1016 individual patients who underwent open microsurgical resection of OGMs. The approaches used included: pterional/unilateral, bifrontal with variations, and anterior interhemispheric approaches. Across all studies, gross total resection (Simpson Grades I or II) was achieved in 91.4% of cases, and subtotal resection (Grades III and IV) was reported in 8.6% of cases. A cumulative twenty-seven percent of surgical OGM patients sustained some form of complications. Minor issues accounted for 22.2% (CSF leak, seizures, infection, transient cranial nerve palsies, hydrocephalus), whereas major issues comprised 4.7% (hemorrhage, ischemic infarct, malignant cerebral edema). We then examined the correlation between these complications and the surgical approach chosen. Among pooled cohort of 426 patients who underwent unilateral approaches, 14% experienced minor complications, and 2.1% experienced major complications. For the mixed cohort of 410 patients who underwent bifrontal approaches, 24.6% experienced minor complications, and 7% experienced major complications. Conclusions: Unilateral approaches appear to have lower complication rates for the resection of OGMs compared to bilateral approaches. However, the extent of resection is not uniformly reported, making it difficult to identify differences. The use of an improved preoperative classification and scoring system can help establish a more coherent system to select the most suitable approach and to uniformly report surgical outcomes, such as EOR and complication rates specific to a given OGM and its surgical approach.